Factors Affecting the Choice of National and Public Hospitals Among Outpatient Service Users in South Korea - Mi-Ryeong Gil PhD; Cheon Geun Choi (SAGE Publishing, 2019)
The present study analyzed factors underlying outpatient service users' choice of national and public (rather than private) hospitals. Based on Andersen's Behavioral Model, we developed a framework that covered needs, enabling, and personal factors. Data of outpatient service usage were obtained from the Korean medical panel survey during 2008 to 2013. Logistic regression analyses were conducted, and results revealed that the rate of national and public hospital use was very low (5.57%), and our model adequately explained variance in service use. Specifically, several demographic factors-older age, low income, national merit and medical care, being chronically ill, and having a disability-were predictive of whether an individual is likely to choose national and public hospitals. We discuss the need to strengthen national and public hospitals' medical services in order to better manage care for low-income vulnerable groups.